Pengaruh Good Corporate Governance dan Kinerja Keuangan Terhadap Harga Saham dengan Kebijakan Deviden sebagai Variabel Pemoderasi - Napisah, Napisah; Deia Soeparyono, Regina (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2023)
The purpose of this study was to determine the effect of good corporate governance and financial performance on stock prices with dividend policy as a moderating variable. The method used in this research is associative quantitative. The population of this study is LQ45 companies listed on the Indonesia Stock Exchange for the 2017-2021 period with a total of 45 companies and using sample criteria so that there are 17 companies. Data analysis in this study used descriptive statistical analysis, panel data regression model estimation, classic assumption test, hypothesis testing and MRA using eviews 10. The results of this study are directors, ROA, and DER have an effect on stock prices, but independent commissioners and EPS do not effect on stock prices. And the moderating variable for dividend policy cannot strengthen the relationship between directors, independent commissioners, DER and EPS, but only the relationship between ROA and stock prices which can be strengthened by dividend policy as a moderator